Wasteland : the secret world of waste and the urgent search for a cleaner future - Franklin-Wallis, Oliver (Hachette Books, 2023)
"An award-winning investigative journalist takes a deep dive into the global waste crisis, exposing the hidden world that enables our modern economy--and finds out the dirty truth behind a simple question: what really happens to what we throw away?"--